Using information and communication technologies in learning activity of preschool-age children - Ovchinnikova Y. E. (Modern education development theory techniques and practice, 2016)
the analysis of the use of information and communication technologies in the sphere of educational activities of children of preschool age on the basis of the method of observation and practical engagement in educational activities of the preparatory group of the kindergarten. A positive impact of ICT use that contributes to the intellectual, creative and all-round personality development of the child; involve the mental activity of children, stimulates the thought processes.
Keywords: мотивация; информационно-коммуникативные технологии; компьютерные игры; мультимедийные презентации; образовательные учреждения; психические процессы; educational institutions; motivation; multimedia presentation; information-communicative technologies; computer games; mental processes; oboustranne development; обостороннее развитие